2018 IEEE Conference on Decision and Control (CDC) 2018
DOI: 10.1109/cdc.2018.8619335
|View full text |Cite
|
Sign up to set email alerts
|

Deep Reinforcement Learning for Event-Triggered Control

Abstract: Event-triggered control (ETC) methods can achieve high-performance control with a significantly lower number of samples compared to usual, time-triggered methods. These frameworks are often based on a mathematical model of the system and specific designs of controller and event trigger. In this paper, we show how deep reinforcement learning (DRL) algorithms can be leveraged to simultaneously learn control and communication behavior from scratch, and present a DRL approach that is particularly suitable for ETC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…Moreover, we assume that network delays fluctuate randomly due to network routing, where their maximum values are known beforehand. Recently, DRL-based networked control methods have been proposed in [13,17]. However, in these researches, it is not assumed that there are network delays.…”
Section: Related Work and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we assume that network delays fluctuate randomly due to network routing, where their maximum values are known beforehand. Recently, DRL-based networked control methods have been proposed in [13,17]. However, in these researches, it is not assumed that there are network delays.…”
Section: Related Work and Contributionmentioning
confidence: 99%
“…It is shown that the DDPG algorithm can solve more than 20 simulated physics tasks. As its applications to control problems, for example, Baumann et al proposed a method to design an event-triggered controller using the DDPG algorithm in [17] and Duan et al proposed the method to master the power grid voltage control problem using not only the DQN algorithm but also the DDPG algorithm in [18].…”
Section: Introductionmentioning
confidence: 99%
“…Event-triggered controllers can also be learned from data without learning a model. Such approaches are proposed, for example, in [12]- [15]. In contrast to those approaches, we use a specific control design and use learning to obtain accurate dynamic models.…”
Section: Related Workmentioning
confidence: 99%
“…Deep RL has been applied successfully to various control applications. Baumann et al (2018) applied the recent success of deep actor-critic algorithms in an event-triggered control scenario. In Lenz et al (2015), the authors combined system identification based on deep learning with model predictive control.…”
Section: Introductionmentioning
confidence: 99%